Isolation and characterization of bacteriophages against Xylella fastidiosa - Domingo-Calap, María L.; Aure, Cristina M.; Navarro-Herrero, Inmaculada; Domingo-Calap, Pilar; Marco-Noales, Ester (2022)
Bacteriophage viruses are a promising tool for preventing and treating bacterial infections. In this sense, phage therapy is an eco-sustainable approach that has the potential to be used as either an alternative or a complement to other strategies for the management of Xylella fastidiosa diseases. The main objective of this work was the search, isolation, selection and characterization of bacteriophages against this phytopathogenic bacterium.